Biodegradasi Petroleum dan Hidrokarbon Eikosana oleh Isolat Bakteri Pseudomonas aeruginosa - Umar, Faiqah (Al-Kimia, 2015)
Biodegradation of petroleum and hydrocarbon eicosane by Pseudomonas aeruginosa isolate. Hydrocarbon are important environmental contaminants in soil and water. These compounds have a potential risk to human health, as many of them are carsinogenic and toxic to marine organisms such as diatome, gasthrophode, mussel, and fish. The purpose of this research was to know the ability of Pseudomonas aeruginosa to degradate the hydrocarbon (petroleum Hundill and eicosane) substrate. Growing test used in two steps, the preculture and culture step. The biodegradation capacity was measured by quantitative and qualitative tests. The essay showed an increasing biodegradation capacitypercentage of bacteria cell mass on hydrocarbon substrate. The percentage on petroleum Hundill substrat as follows; log phase was 51,6%, descelerate phase was 73%, and linear phase was 81,4%. On eicosane substrate as follows; log phase was 62,7%, descelerate phase was 85,2%, and linear phase was 85,2%. The qualitative biodegradation capacity by chromatography result showed separate enchained of carbon n-alkana in each growth phase on petroleum Hundill substrate. Carbon chain termination as follows; C11, C12, C14, C15, C16, C18, C22 on log phase, C12, C17, C19, C20, C24 on descelerate phase, and C12 until C25 even better on linear phase.